The Multiple Influences on the Future of Work in Agriculture: Global Perspectives - Dedieu, Benoit; Contzen, Sandra; Nettle, Ruth; Schiavi, Sandra Mara de Alencar; Sraïri, Mohamed Taher (Frontiers in Sustainable Food Systems, 2022)
Work in agriculture is changing, influenced by a large variety of factors: global food chains and societal controversies on farming models, the status of agricultural work as a profession alongside others; the progress of rural development; issues of precarity in work and in health. We summarize these influences and their implications in this introduction of the Special Issue “Work in agriculture: which perspectives?”, and delineate the eight papers that contribute to understanding of the future trajectories for work in agriculture.